Rabiah al-Adawiyah dan Mahabbah Al-Ghazali - N, Nurbaya; Abbas, Nurlaelah; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article discusses true love, obedience and submission to Allah SWT, obedience and obedience in worshiping Allah is the first step for humans to attain spiritual peace and true love. Rabi'ah Al-Adawiyah was the first very famous female Sufi figure, Rabiah Al-Adawiyah in her Sufism journey always worshiped solely out of love for Allah SWT without expecting reward, heaven or because she was afraid of the threat of hell if she did not obey His commands. However, in contrast to Imam Al-Ghazali who later considered that love was born gradually through a process, namely with knowledge, a life journey based on experience and so on, Al-Ghazali viewed that love for Allah is the peak of deep knowledge, awareness of the presence of Allah by carrying out dhikr worship and through cleansing the soul, a calm soul is a soul that has been freed from lust, anxiety and love of the world so that calm comes from a form of sincerity in worship and trust.